2018
DOI: 10.1111/jocn.14224
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a pain management nursing protocol for orthopaedic surgical patients: Results from a PAIN OUT project

Abstract: It was feasible to develop and implement a standardised pain management nursing protocol and use it in the clinical routine. The intervention had an effect on changing some features of care, with an improvement in patient-reported outcomes. Support by leaders and medical team facilitated the process of the implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…These studies reported significantly increased use of morphine by 12.7% ( P < .05) and tramadol by 12.0% ( P < .05), as well as reduced pain intensity; however, no changes in opioid‐related ADEs or LOS were shown. In contrast, 4 studies used pain scales to assess pain severity and provide treatment using multimodal strategies including nonpharmacological and nonopioid methods . The use of opioid analgesics varied in these studies, however, significantly increased use of nonpharmacological pain management (60.0 vs 96.0%; P < 0.05) and nonopioid analgesia (38.8 vs 66.2%; P < 0.05) were reported .…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…These studies reported significantly increased use of morphine by 12.7% ( P < .05) and tramadol by 12.0% ( P < .05), as well as reduced pain intensity; however, no changes in opioid‐related ADEs or LOS were shown. In contrast, 4 studies used pain scales to assess pain severity and provide treatment using multimodal strategies including nonpharmacological and nonopioid methods . The use of opioid analgesics varied in these studies, however, significantly increased use of nonpharmacological pain management (60.0 vs 96.0%; P < 0.05) and nonopioid analgesia (38.8 vs 66.2%; P < 0.05) were reported .…”
Section: Resultsmentioning
confidence: 90%
“…Fifteen interventions involved surgical inpatients, 3 were implemented in the intensive care unit, 7 were conducted in the ED, 5 involved geriatric inpatients (≥65 years), and the remaining 7 studies were conducted in all inpatients, and those receiving patient‐controlled analgesia (PCA) or transdermal fentanyl …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations